Identification of Time Wastage Towards Lean Production for IBS: A Case Study of Precast Hollow Core Slab Production - Rohaida, Affandi; Izni Syahrizal, Ibrahim; Masine, Md Tap; Aliff Ridzuan, Bunawan (International Information and Engineering Technology Association (IIETA), 2025)
The introduction of Industrialized Building System (IBS) is thought to hasten the construction process when it is substituted from the traditional cast-in-place approach to the factory-made precast component. Since IBS components manufacturing may boost its productivity using Lean Production to cut down on-time wastage, there is a clear need to investigate their manufacturing efficiency in the construction industry. In this paper, the time wastage of manufacturing precast hollow core slab is placed under close inspection to assess areas of improvements. Upon developing the Value Stream Mapping (VSM) of the manufacturing process, the research then investigates the root cause of the time wastage by employing major waste checklist and then proceeds to develop an Ishikawa Diagram to better illustrate the findings. To give proper weightage and comparative priority for improvements, the Cause-and-Effect Matrix (CEM) method is applied and then described by a Pareto chart. The root cause of time wastage was then pointed out to be inefficient machinery utilization and traditional procedure in the bed cleaning process. Several corrective measures are then suggested to reduce time wasting in the production of precast hollow core slab.